2014
DOI: 10.1186/s13047-014-0047-4
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms in people with diabetes attending outpatient podiatry clinics for the treatment of foot ulcers

Abstract: BackgroundThe purpose of this study was to examine the prevalence of depressive symptoms, diabetes self-management, and quality of life in people with diabetes and foot ulcers. Ulcer status, mortality and amputations were also assessed at six months follow-up.MethodsThis was a cross-sectional survey of people attending outpatient podiatry clinics at a major tertiary referral hospital. Depressive symptoms were measured using the Patient Health Questionnaire (PHQ). Diabetes self-care was assessed using the Summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Schunk et al (19) evaluated many variables, such as age, gender, duration of DM, use of insulin, and body mass index using the SF-12 as a measure of QOL. Several other studies have used the SF-12 as an outcome instrument for patients with diabetic foot ulcers (16,18,20). Many other studies of QOL in diabetic foot disease have used the SF-36 as an outcome instrument (3,2127).…”
Section: Discussionmentioning
confidence: 99%
“…Schunk et al (19) evaluated many variables, such as age, gender, duration of DM, use of insulin, and body mass index using the SF-12 as a measure of QOL. Several other studies have used the SF-12 as an outcome instrument for patients with diabetic foot ulcers (16,18,20). Many other studies of QOL in diabetic foot disease have used the SF-36 as an outcome instrument (3,2127).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, diabetic patients who suffer from depression are twice as likely to develop a chronic foot ulcer, and depression is also a risk factor for infection in the chronic wound . Depression and cognitive impairment are associated with decreased treatment compliance and adherence to self‐care tasks . Treatment compliance and persistent self‐care are critical for optimal wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that a third of people with diabetic foot ulcers suffer from clinical depression. Depressive symptoms are associated with more compromised overall diabetic self-care and health-related quality of life (Pearson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%